Assessing and screening preschoolers : psychological and educational dimensions (Allyn and Bacon, 1999)
This book is divided into six parts: Introduction; Normal, Delayed, and Different development of Preschool; Ethical and technical issues in preschool assessment; Assessment of major realms of functioning; Evaluating special populations; and Writing and implementing assessment results.